Implementation of Storytelling Method to Improve Receptive Language Development in Grade 2 Children at Cengklik Surakarta State Elementary School - Septianti, Trisna Cahya; Putri, Anggi Resina; Setyaningsih, Wiwik (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Children are part of the younger generation. Acceptance from the family environment is the primary basis for children to grow and develop well. At school, children often communicate through storytelling activities with teachers and friends. Stories make it easier for children to understand knowledge. Stories for children can be a means to increase children's vocabulary and build a network of expertise within children. The storytelling method has many advantages, including spurting children's verbal abilities and linguistic intelligence and encouraging children to enjoy listening to stories and telling or talking (Syafi'i & Gumiandari, 2023). Storytelling is part of receptive language because, in this ability, the meaning of language is obtained and processed through visual and verbal symbols taught. However, many students in grade 2 of elementary school still need to achieve the expected abilities (Setiyaningsih et al., 2023). Knowing the Implementation of Storytelling Method to Improve Receptive Language Development in Grade 2 Children at Cengklik Surakata State Elementary School. This study uses a research design called